Karen Horney's theories of neurosis : an empirical clinical study - Jenner, Shirley Anne (Department of Psychology, 2026)
Karen Horney's theory of neurosis was presented. Her typology of neurotic defensive solutions, which is formulated in her later theory, was empirically tested with 25 neurotic subjects and 24 controls differentiated by the M.M.P.I. Behaviour was tested clinically by the use of interviews and by the use of the Rorschach test. Klopfer, Elizur's Anxiety and Hostility level and R.I.R.S. scores were analysed to reveal any differences in behaviour between members of the different neurotic solution categories. Statistics used were the Anova test, and the Fisher Exact Probability test. No evidence was found for the existence of the Horneyan neurotic typology.